1992
DOI: 10.1113/jphysiol.1992.sp019395
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation characteristics of a sustained, Ca(2+)‐independent K+ current of rat hippocampal neurones in vitro.

Abstract: SUMMARY1. Current or voltage clamp recordings from CA3 neurones of the adult rat hippocampal slice were performed to study the inactivation properties of a slow outward K+ current identified as the delayed rectifier (IK).2. In current clamp experiments, burst firing evoked from resting membrane potential by intracellular current injection was reduced or blocked by conditioning hyperpolarizing pre-pulses of 20-40 mV amplitude. This effect was inhibited by tetraethylammonium (TEA; 20 mM) but was unaffected by Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In keeping with previous studies (Sim and Cherubini, 1990;Neuman et al, 1991;Nistri and Cherubini, 1992), CA3 neurons fromjuvenile and adult rats had a resting membrane potential more negative than -55 mV, spike overshoots of 10-15 mV and a resting input resistance of 54 + 14 MQ (ranging from 28 to 83 MQ, n = 42). This value was significantly different (P < 0.05) from that found at PO-P6.…”
Section: P7-p31supporting
confidence: 88%
“…In keeping with previous studies (Sim and Cherubini, 1990;Neuman et al, 1991;Nistri and Cherubini, 1992), CA3 neurons fromjuvenile and adult rats had a resting membrane potential more negative than -55 mV, spike overshoots of 10-15 mV and a resting input resistance of 54 + 14 MQ (ranging from 28 to 83 MQ, n = 42). This value was significantly different (P < 0.05) from that found at PO-P6.…”
Section: P7-p31supporting
confidence: 88%
“…In immature CAI pyramidal cells a fast inactivating component is dominant (Spigelman et al 1992). It has previously been shown that the slowly inactivating component can become activated either very slowly, reaching peak amplitude within several hundred milliseconds (Segal & Barker 1984, Numann et al 1987Nistri & Cherubini, 1992), or with a fast time course of a few milliseconds (Halliwell et al 1986;Sah, Gibb & Gage, 1988;Ficker & Heinemann, 1992). Under our experimental conditions, the a 1-5 6 1 -0 1 40 mV ensemble current reached its peak value with a time constant close to 2 ms, and a slowly activating component was never observed.…”
Section: Discussionmentioning
confidence: 45%
“…Initially, there is a large outward current component that inactivates in ϳ100 ms to a sustained plateau; these two components are due, respectively, to activation of I K(Ca) and activation of I K(V) . I K(Ca) are activated by the [Ca 2ϩ ] c transient generated by the prepulse and inactivate upon clearance of such transient to give rise to the sustained plateau, that is due to voltage-dependent K ϩ channels, which remain open for the entire 400-ms depolarizing pulse (52). Figure 2E shows that the I K(Ca) and I K(V) components of I K were present in mSOD1 cells; they, however, were substantially lower than those recorded in the WT cell.…”
Section: Resultsmentioning
confidence: 99%